IDENTIFIKASI PROFIL KARAKTERISTIK MORFOLOGI SPORA DAN PROTHALIUM TUMBUHAN PAKU FAMILIA POLYPODIACEAE - N. Nurchayati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2016)
Fern is a vascular plant wich classified to the low level plants. Polypodiaceae is family of ferns with high diversity in the world. Ferns have sporophytes and gametophytes generation independently. In addition to morphology os sphorophytes, morphology’s gametophytes of ferns in form spores and prothallium also have potential diversity.of characters. That diversity need to be done research to identify the profile of spores dan prothallium characteristic of ferns in the Polypodiaceae family. The aim of this research is to identify the profile of spores dan prothallium characteristic of ferns in the Polypodiaceae family. The research method is conducted in stage: 1) takeing sample of 10 species Polypodiaceae family of ferns. These species is Adiantum caudatum, Asplenium nidus,Athyrium sp, Dryopteris concolor, Nephrolepis falcata, Phymatodes longissima, Pityrogramma calomelanos, Platycerium bifurcatum, Pteris ensiformis, Pyrrosia sp, 2) planting spores to produce prothallium, 3) observe the morphological spores and prothallium. Result of this research shows that spores of 10 species were observed have various form, that is include: ovatus, elipticus, reniformis, triangularis and serial irregular. Variety of surface ornamentation spores include: retiformis foveatus, granulosus, ruminatus, verruculosus, colliculotus, areolatus, and glabber. Prothallium of these species have elongated cordata and widened cordata shapes. The difference is showed on the edge of prothallium and the presence of additional part likes papila and trichomes on its surface. The layout of the anteredia of Platycerium bifurcatum and Pyrrosia sp is different from the others, which is located on the edge of the surface prothallium. The archegonia of all species is located near the notch of prothallium. Diversity characters of spores and prothallium can be use to classification and analysis of realationship of fern. Key words: Ferns, spore, prothallium, character, diversity